348P Malignant melanoma: A study of clinical profiles and treatment outcomes in Indian patients. (24th November 2019) - Shishak, S A; Rastogi, S; Pandey, R; Barwad, A; Dhamija, E; Aggarwal, A; Kalra, K; Shamim, S A; Parisa, M
Abstract: Background: Malignant melanoma is an extremely rare malignancy in the Indian subcontinent and South east Asia. Its already known that Asian countries have different clinical presentation of melanoma. It would be interesting to know the epidemiology and outcome of advanced disease in Indian patients. Methods: We retrospectively analysed patients with malignant melanoma who were registered in Medical Oncology clinic at AIIMS, New Delhi between January 2016 and July 2019. We used SPSS version 23 for analysis. Immunotherapy used was single agent Nivolumab as Ipilimumab is unavailable. Results: Total of 93 patients (57 males, 36 females) were registered in the study. Median age was 53 (range, 25 to 85 years), with the commonest primary sites being anorectal (n = 23) and foot (n = 23), followed by eye (n = 15), head and neck (n = 12), thigh (n = 9), others (n = 11) respectively. The commonest sites of metastasis were lymph nodes (n = 54, 58.1%), lung (n = 45, 48.4%), liver(n = 33, 35.5%) and bone(n = 25, 26.9%).The median sites of metastasis was two (range 1-5). Most patients had ECOG PS 1-2 (n = 77, 82.8%). Majority of the patients (n = 80, 86%) had metastasis.Out of 93 patients, 39(42%) received chemotherapy in first line, 16 (17.3%) received Immunotherapy, 13 (13.9%) underwent surgery and best supportive care was offered to 25 (26.8%) patients. The chemotherapy used were dacarbazine (n = 27), nabpaclitaxel (n = 6) and others (n = 6). Among patients who received chemo, median number of cycles was 5 (range, 1-15) and response assessment revealed progressive disease in 17 patients, stable disease in 4 patients, partial response in one patient, and remaining 16 patients defaulted and were not evaluable. Among patients who received Single agent Nivolumab, the median number of cycles was 5 (range, 2-15) and response showed progressive disease in all patients, except one. Median follow up was 18 months and median PFS was 3 months. Conclusions: This study shows that the site of melanoma in Indian patients is different as compared to western patients with higher number of anorectal, mucosal and acral melanoma. Immunotherapy was feasible for only a fraction of patients in view of exorbitant cost. Non availability of BRAF therapies and Ipilimumab is of great concern in view of poor outcomes. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.